2009
DOI: 10.1136/thx.2008.095547
|View full text |Cite
|
Sign up to set email alerts
|

School age outcome of hospitalisation with respiratory syncytial virus infection of prematurely born infants

Abstract: Background: Hospitalisation due to respiratory syncytial virus (RSV) infection in the first 2 years after birth has been associated with increased healthcare utilisation and associated costs up to 5 years of age in children born prematurely at less than 32 weeks of gestation who developed bronchopulmonary dysplasia (BPD). A study was undertaken to determine whether hospitalisation due to RSV infection in the first 2 years was associated with increased morbidity and lung function abnormalities in such children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 32 publications
0
68
0
2
Order By: Relevance
“…Increased clinical care for preterm infants hospitalised with RSV translates to increased morbidity, healthcare utilisation and costs of care for respiratory illnesses later in life [65,66]. Early-life hospitalisation with RSV infection among preterm infants has been associated with more than a 2-fold increase in the mean number of subsequent hospitalisations during the 4 years following the initial infection (1.28 vs. 2.96; P  < 0.001), when compared with non RSV-related hospitalisation [67].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 3 more Smart Citations
“…Increased clinical care for preterm infants hospitalised with RSV translates to increased morbidity, healthcare utilisation and costs of care for respiratory illnesses later in life [65,66]. Early-life hospitalisation with RSV infection among preterm infants has been associated with more than a 2-fold increase in the mean number of subsequent hospitalisations during the 4 years following the initial infection (1.28 vs. 2.96; P  < 0.001), when compared with non RSV-related hospitalisation [67].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Even though the majority of the data on the long-lasting impact of RSV have been based on studies of healthy term-born infants, limited studies have demonstrated increased risk of asthma [68], recurrent wheeze [34,69,70] and lung function impairments [66] in preterm children with a history of RSV-related hospitalisation during infancy. Early-life hospitalisation with RSV infection in preterm infants has been associated with more than twice the risk of ongoing respiratory morbidity, with wheezing rates ranging from 20.7 to 42.8%, 1–2 years following RSV-related hospitalisation compared to 4.1 to 23% following non-RSV related hospitalisation [43].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Following discharge from the neonatal intensive care unit (NICU), surviving preterm infants with subsequent VRTIs are more likely to develop severe respiratory disease or suffer from recurrent wheeze and asthma [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%